PEMETAAN JARINGAN DISTRIBUSI (SUTM) 20 kV DAN PERKIRAAN KEBUTUHAN LISTRIK DI KECAMATAN PAYUNG SEKAKI, KABUPATEN SOLOK - Surfa Yondri; Witrionanda witrionanda; A fadly (Teknik Elektro Politeknik Negeri Padang, 2013)
Payung Sekaki district is one of the area in Solok Region that needs the development of electricity network. To support its development plan, the real condition of Payung Sekaki district should be known. The mapping method is one of the way to know the already implemented electricity area.Based on the mapping result, it is known that the electricity network of SUTM 20 kV at Payung Sekaki district has been implemented in Sikrukam area and Supayang area and not yet in Aie Luo area. The estimation method of electricity needs at Payung Sekaki district is motivated to get information on its development based on economic and population growth. Data processing results using SPSS show that the eletricity needs at Payung Sekaki district from 2013 to 2014 will dramatically increase followed by the increasing of economic growth in spite of population growth is still remain the same.